MODEL INTEGRATIF MANAJEMEN MUTU PENDIDIKAN DASAR: A SYSTEMATIC LITERATURE REVIEW - Fatkhurrohman Fatkhurrohman; Atiqoh Atiqoh; Rasad Mulyadi; Encep Syarifudin; Eneng Muslihah; Siti Patimah (STKIP Pesisir Selatan, 2026)
Improving the quality of primary education is a strategic agenda in developing quality human resources. Various studies indicate that educational quality is influenced by factors such as principal leadership, teacher competence, school culture, infrastructure, and community participation. However, most previous studies examined these factors partially, resulting in the absence of a comprehensive quality management model. This study aims to analyze the main factors affecting primary education quality and to develop an integrative quality management model based on a synthesis of recent research. The study employs the Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Articles were obtained from Scopus, ERIC, Dimensions, and Google Scholar databases for the period 2020-2026. After identification, screening, and eligibility assessment, 35 articles meeting the inclusion criteria were obtained. The results show that transformational leadership of principals is the main driving factor influencing teacher competence improvement, positive school culture formation, infrastructure optimization, and community participation strengthening. The findings produce the Integrative Model of Primary Education Quality Management (MIMPD), which places school leadership as the main catalyst for improving learning quality and student achievement. This study provides a conceptual contribution in the form of a synthesis model that can be used as a basis for policy development and quality management practices in Indonesian primary education.